Neuroscience and ethnography: an interdisciplinary revision and a cognitive proposal based on compassion research in Mexico - Roberto E. Mercadillo (Universidad de San Buenaventura, 2013)
Social neuroscience considers the interplay of biologically evolved mechanisms and culturally shaped experiences as decisive to contextualize, motivate and influence complex brain functions and cognition. Compassion is a suitable moral emotion for approaching social cognition because it involves naturally and socially evolved factors to empathize with and wish to alleviate a perceived suffering of other individuals, and thereby promote social welfare. The present paper outlines research projects performed in Mexico, which focused on compassion from different viewpoints. The analysis includes psychometric evaluations of emotional appraisals, ethnographic records of Mayan populations, functional brain imaging with healthy Mexican individuals, including a sample of police officers’, and theoretical analysis relating compassion and violence. We propose a threefold neurocognitive compassion system encompassing empathy, executive functions and memory. Also, we suggest applying ethnographic methods to design neuroimaging studies and thereby reveal and interpret brain functions among different social and cultural groups.